Co-assembly of graphene/polyoxometalate films for highly electrocatalytic and sensing hydroperoxide - Bao, Yayan; Chen, Zezhong; Wang, Yuzhen; Liu, Lizhen; Wang, Haiyan; Li, Zuopeng; Feng, Feng (Frontiers in Chemistry, 2023)
Graphene oxide (GO) films mixed with polyethylenimine (PEI) were prepared by a layer-by-layer assembly (LBL) method, in which the GO component is then converted to reduced GO (rGO) in situ through an electron transfer interaction with a polyoxometalate (POM) that is assembled on the outer surface. With this, devices were manufactured by spreading composite films of (PEI/rGO)n-POM with different numbers of PEI/rGO layers on ITO substrates. Cyclic voltammetry (CV) reveals that the catalytic activity for H2O2 of (PEI/rGO)n-POM films was significantly higher than that of similar films of (PEI/GO)n/PEI/POM manufactured LBL with the same number of layers, although the catalyst POM content of (PEI/rGO)n-POM was only half that of (PEI/GO)n/PEI/POM. The catalytic activity of (PEI/rGO)n-POM films first increases and then decreases as the number of PEI/rGO layers increases. The result shows that (PEI/rGO)3-POM films with three PEI/rGO layers exhibit the highest efficiency. Amperometric measurements of the (PEI/rGO)3-POM films showed improved current response, high sensitivity, wide linear range, low detection limit, and fast response for H2O2 detection. The enhanced catalytic property of (PEI/rGO)n-POM films is attributed to the electron transfer interaction and electrostatic interaction between POM and rGO.